Lightweight heat-insulating cellulose nanofiber aerogel and preparation method thereof

By performing multi-step homogenization, freeze-drying and cross-linking treatment in the preparation process of cellulose nanofiber aerogel, the problem of cellulose nanofibers prone to entanglement in the freeze-forming process is solved, and the mechanical properties and thermal insulation properties of the aerogel are improved.

CN119842113AActive Publication Date: 2025-04-18DONGHUA UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510079584.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-18
Estimated Expiration
2045-01-18

AI Technical Summary

Technical Problem

The existing aerogels for heat insulation have problems such as poor flexibility and low strength, and cellulose nanofibers are prone to entanglement with each other during the freezing molding process, resulting in the microstructure from 1D to 2D, reducing the elasticity and strength of the aerogel.

Method used

By homogenizing the cellulose nanofibers in water and lyophilized, a lyophilized cellulose nanofiber aerogel was obtained, and on this basis, secondary homogenization, stand-alone pre-crosslinking, freeze-drying and cross-linking treatment was performed to form a lightweight thermally insulated cellulose nanofiber aerogel.

Benefits of technology

This method can maintain the fiber structure of cellulose nanofibers, improve the mechanical properties, elasticity and compression cycle properties of the aerogel. The thermal conductivity is 0.028-0.040W/(m·k), the density is 1.5-20mg/cm3, the compression strength is 1-18kPa, and the rebound rate is more than 80% after 100 compressions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842113A_ABST
    Figure CN119842113A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional aerogel, and provides lightweight heat-insulating cellulose nanofiber aerogel and a preparation method thereof. The method comprises the following steps: homogenizing cellulose nanofibers in water, and freeze-drying a cellulose nanofiber dispersion liquid to obtain freeze-dried cellulose nanofiber aerogel; homogenizing the freeze-dried cellulose nanofiber aerogel in water, stirring and mixing a secondary cellulose nanofiber dispersion liquid, a cross-linking agent and silane, and sequentially carrying out standing pre-cross-linking, freeze-drying and cross-linking treatment, so as to obtain the light heat-insulating cellulose nanofiber aerogel. According to the method for preparing the light heat-insulation cellulose nanofiber aerogel through secondary molding, the fiber structure of cellulose nanofibers can be kept, the phenomenon of mutual entanglement of cellulose is reduced, the mechanical property, rebound resilience and compression cycle performance of the aerogel are improved, and the light heat-insulation cellulose nanofiber aerogel is prepared. The prepared cellulose nanofiber aerogel has a good application prospect in the field of thermal insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional aerogels, and in particular to a lightweight heat-insulating cellulose nanofiber aerogel and a preparation method thereof. Background Art

[0002] With the improvement of people's living standards, the thermal insulation function of traditional thermal insulation materials can no longer meet people's demand for quality of life. For example, the requirements of various industries for various types of thermal insulation materials are becoming increasingly diversified and focus on multi-faceted balance. Thermal insulation materials not only need to ensure basic thermal insulation performance, but also need to be light, thin, highly elastic and breathable. Aerogel is a nanoporous material with ultra-low density and a highly cross-linked network structure. The liquid inside the wet gel is replaced by air, so the aerogel contains a large amount of air. Based on the above structural characteristics, aerogel has many advantages, such as high specific surface area, high porosity, low thermal conductivity, low density and 3D interconnected nanoporous network structure. It stands out among porous materials and is considered to be one of the thermal insulation materials with great application prospects. At present, aerogels used in the field of thermal insulation are mainly used as interlayers between substrates and coatings of buildings, automobiles or electronic products, or ground into nanoparticles and sprayed on the surface of the substrate.

[0003] In the field of thermal insulation, aerogels generally have disadvantages such as poor strength, poor toughness, and difficulty in processing. Cellulose has the characteristics of abundant raw materials, non-toxicity, easy modification, and good biocompatibility. It can be modified to give cellulose better mechanical properties and resilience, and has good prospects in the field of thermal insulation. The development of thermal insulation aerogels that are easy to process, have good mechanical properties, and are low in cost has become the top priority of aerogel research and development in the field of thermal insulation.

[0004] In addition, the microstructure of the cellulose nanofiber dispersion is a typical 1D nanofiber structure. When the cellulose nanofiber dispersion is prepared by traditional freeze drying to obtain a cellulose nanofiber aerogel, the cellulose nanofibers will be entangled with each other, causing the microstructure to be changed from 1D nanofibers to 2D sheet structures, which to a certain extent reduces the resilience and strength of the aerogel. Therefore, how to keep the cellulose nanofibers still in the 1D nanofiber structure during the freezing molding process, and then improve their mechanical properties, is a problem that needs to be solved urgently. CN118791781A discloses a thermal insulation material obtained by directly mixing oxidized cellulose and polyvinyl alcohol and freeze-drying. The material has high compression strength and a simple and convenient preparation process. The disadvantage is that the cellulose is directly entangled with the polyvinyl alcohol into a sheet, the porosity is low, and the aerogel density is too large, which further reduces its thermal insulation performance.

[0005] Therefore, it is of great value to study a method for preparing a lightweight insulating cellulose nanofiber aerogel with good thermal insulation, mechanical properties and resilience. Summary of the invention

[0006] The purpose of the present invention is to provide a lightweight thermal insulation cellulose nanofiber aerogel and a preparation method thereof in order to overcome the deficiencies of the prior art, so as to solve the technical problems of poor flexibility and low strength of the current thermal insulation aerogel.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a lightweight thermal insulating cellulose nanofiber aerogel, comprising the following steps:

[0009] 1) homogenizing cellulose nanofibers in water to obtain a cellulose nanofiber dispersion, and freeze-drying the cellulose nanofiber dispersion to obtain a freeze-dried cellulose nanofiber aerogel;

[0010] 2) The freeze-dried cellulose nanofiber aerogel is homogenized in water to obtain a secondary cellulose nanofiber dispersion, and the secondary cellulose nanofiber dispersion, a cross-linking agent and silane are stirred and mixed, and then subjected to static pre-cross-linking, freeze-drying and cross-linking treatment in sequence to obtain a lightweight thermal insulating cellulose nanofiber aerogel.

[0011] Preferably, in the cellulose nanofiber dispersion in step 1), the mass fraction of cellulose nanofibers is 0.01-0.15%.

[0012] Preferably, the cellulose nanofibers in step 1) are gel-like cellulose nanofibers, and the mass content of the cellulose nanofibers in the gel-like cellulose nanofibers is 2.5-3.5%.

[0013] Preferably, the homogenization time in step 1) and step 2) is independently 15 to 45 minutes, and the homogenization speed is independently 3000 to 15000 r / min.

[0014] Preferably, the freeze-drying in step 1) and step 2) comprises pre-freezing and vacuum freeze-drying in sequence, wherein the pre-freezing temperature is -196 to -150°C, and the pre-freezing time is 10 to 60 minutes; the vacuum freeze-drying temperature is -85 to -75°C, and the vacuum freeze-drying time is 48 to 96 hours, and the vacuum degree of the vacuum freeze-drying is 0.5 to 20Pa.

[0015] Preferably, in step 2), the solid content of the secondary cellulose nanofiber dispersion is 0.1-1%, the mass ratio of the crosslinking agent to the cellulose nanofiber is 1:5-20, and the volume mass ratio of the silane to the cellulose nanofiber is 1 mL:3.5-10 g.

[0016] Preferably, in step 2), the cross-linking agent comprises one or more of butanetetracarboxylic acid, isocyanate, glutaraldehyde and citric acid; and the silane comprises one or more of methyltrimethoxysilane, dodecyltrimethoxysilane and perfluorodecyltrichlorosilane.

[0017] Preferably, the temperature of the cross-linking treatment in step 2) is 90 to 140° C., and the time of the cross-linking treatment is 3 to 12 hours.

[0018] The present invention also provides a lightweight thermal insulating cellulose nanofiber aerogel prepared by the preparation method of the lightweight thermal insulating cellulose nanofiber aerogel, wherein the thermal conductivity of the lightweight thermal insulating cellulose nanofiber aerogel is 0.028 to 0.040 W / (m·k) and the density is 1.5 to 20 mg / cm 3 .

[0019] The beneficial effects of the present invention include the following:

[0020] 1) The method for preparing the lightweight thermal insulating cellulose nanofiber aerogel of the present invention can maintain the fiber structure of the cellulose nanofibers, reduce the phenomenon of entanglement between cellulose fibers, and improve the mechanical properties, resilience and compression cycle performance of the aerogel.

[0021] 2) The thermal conductivity of the lightweight thermal insulating cellulose nanofiber aerogel prepared by the method of the present invention is 0.028-0.040 W / (m·k) and the density is 1.5-20 mg / cm 3 The compression strength is 1 to 18 kPa, and after 100 compressions, the rebound rate is more than 80%. The cellulose nanofiber aerogel prepared by the method of the present invention has good application prospects in the field of thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the cellulose nanofiber aerogel prepared by secondary molding in Example 1;

[0023] Figure 2 This is a SEM image of the cellulose nanofiber aerogel obtained by conventional freeze drying in Comparative Example 1;

[0024] Figure 3 This is the cyclic compression curve of the cellulose nanofiber aerogel prepared by the secondary molding in Example 1;

[0025] Figure 4 This is the cyclic compression curve of the cellulose nanofiber aerogel obtained by conventional freeze-drying in Comparative Example 1. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a lightweight thermal insulating cellulose nanofiber aerogel, comprising the following steps:

[0027] 1) homogenizing cellulose nanofibers in water to obtain a cellulose nanofiber dispersion, and freeze-drying the cellulose nanofiber dispersion to obtain a freeze-dried cellulose nanofiber aerogel;

[0028] 2) The freeze-dried cellulose nanofiber aerogel is homogenized in water to obtain a secondary cellulose nanofiber dispersion, and the secondary cellulose nanofiber dispersion, a cross-linking agent and silane are stirred and mixed, and then subjected to static pre-cross-linking, freeze-drying and cross-linking treatment in sequence to obtain a lightweight thermal insulating cellulose nanofiber aerogel.

[0029] In the present invention, in the cellulose nanofiber dispersion in step 1), the mass fraction of cellulose nanofibers is preferably 0.01 to 0.15%, more preferably 0.05 to 0.12%, and even more preferably 0.06 to 0.1%.

[0030] In the present invention, the cellulose nanofibers in step 1) are preferably gel-like cellulose nanofibers, and the mass content of the cellulose nanofibers in the gel-like cellulose nanofibers is preferably 2.5 to 3.5%, more preferably 2.8 to 3.2%, and even more preferably 3%.

[0031] In the present invention, the homogenization time of step 1) and step 2) is preferably 15 to 45 minutes, more preferably 20 to 40 minutes, and more preferably 30 to 35 minutes. The homogenization speed is preferably 3000 to 15000 r / min, more preferably 4000 to 12000 r / min, and more preferably 6000 to 7000 r / min.

[0032] 10000r / min.

[0033] In the present invention, the freeze-drying in step 1) and step 2) preferably comprises pre-freezing and vacuum freeze-drying in sequence, the pre-freezing temperature is preferably -196 to -150°C, more preferably -190 to -165°C, more preferably -180 to -170°C, the pre-freezing time is preferably 10 to 60 min, more preferably 20 to 50 min, more preferably 30 to 40 min; the vacuum freeze-drying temperature is preferably -85 to -75°C, more preferably -82 to -78°C, more preferably -80°C, the vacuum freeze-drying time is preferably 48 to 96 h, more preferably 55 to 80 h, more preferably 60 to 70 h, the vacuum degree of vacuum freeze-drying is preferably 0.5 to 20 Pa, more preferably 1 to 15 Pa, more preferably 3 to 10 Pa.

[0034] In the present invention, the solid content of the secondary cellulose nanofiber dispersion in step 2) is preferably 0.1-1%, more preferably 0.3-0.8%, and more preferably 0.5-0.6%; the mass ratio of the crosslinking agent to the cellulose nanofiber is preferably 1:5-20, more preferably 1:8-18, and more preferably 1:9-15, and the volume mass ratio of silane to cellulose nanofiber is preferably 1 mL:3.5-10 g, more preferably 1 mL:4-8 g, and more preferably 1 mL:5-7 g.

[0035] In the present invention, the cross-linking agent in step 2) preferably comprises one or more of butanetetracarboxylic acid, isocyanate, glutaraldehyde and citric acid; the silane preferably comprises one or more of methyltrimethoxysilane, dodecyltrimethoxysilane and perfluorodecyltrichlorosilane.

[0036] In step 2) of the present invention, the secondary cellulose nanofiber dispersion, crosslinking agent, silane and sodium hypophosphite are preferably stirred and mixed, and the mass ratio of sodium hypophosphite to cellulose nanofibers in the gel-like cellulose nanofibers is preferably 1:25-100, more preferably 1:40-90, and more preferably 1:45-75.

[0037] In the present invention, the static pre-crosslinking time in step 2) is preferably 22 to 30 hours, and more preferably 24 to 28 hours.

[0038] In the present invention, the temperature of the cross-linking treatment in step 2) is preferably 90-140°C, more preferably 100-130°C, more preferably 110-120°C, and the time of the cross-linking treatment is preferably 3-12h, more preferably 4-10h, more preferably 5-8h.

[0039] In the present invention, the cross-linking treatment is preferably a first cross-linking treatment and a second cross-linking treatment in sequence. The temperature of the first cross-linking treatment is preferably 90-100°C, more preferably 95°C, and the time of the first cross-linking treatment is preferably 1-2h; the temperature of the second cross-linking treatment is preferably 125-130°C, more preferably 127-128°C, and the time of the second cross-linking treatment is preferably 3-10h, more preferably 3-6h.

[0040] In the present invention, the cross-linking treatment is performed under a vacuum environment, and the vacuum degree of the vacuum environment is preferably 0.8 to 1.2 Pa, more preferably 0.9 to 1.1 Pa, and even more preferably 1.0 Pa.

[0041] The present invention also provides a lightweight thermal insulating cellulose nanofiber aerogel prepared by the preparation method of the lightweight thermal insulating cellulose nanofiber aerogel, wherein the thermal conductivity of the lightweight thermal insulating cellulose nanofiber aerogel is 0.028 to 0.040 W / (m·k) and the density is 1.5 to 20 mg / cm3 .

[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0043] In the embodiment of the present invention, butane tetracarboxylic acid is produced by Shanghai BiDe Pharmaceutical Technology Co., Ltd. with a purity of 98%; the gel-like cellulose nanofibers are provided by Tianjin Mujingling Biotechnology Co., Ltd., model PL5, are milky white gel-like, have a sodium carboxylate content of 1.4 mmol / g, and the length of the cellulose nanofibers is 1 to 5 μm, and the fiber diameter is 10 to 20 nm.

[0044] The calculation formula of aerogel density is: Where ρ represents the density of aerogel (mg / cm 3 ), m represents the mass of aerogel (mg), v represents the volume of aerogel (cm 3 ). The instrument used for the aerogel compression stress test is the Exceed 40 universal testing machine of Mesite Company of the United States, which is set to a uniaxial quasi-static compression stress-strain test with a load loading rate of 30 mm / min. The thermal conductivity test instrument of the aerogel is the TPS2500 thermal analyzer of Hot Disk Company of Sweden, and the test method is set to the steady-state heat source method.

[0045] Example 1

[0046] 4 g of gelatinous cellulose nanofibers (the mass fraction of cellulose nanofibers is 3%) were added to 200 g of deionized water, and homogenized and stirred at a speed of 4000 r / min for 30 min to obtain a primary cellulose nanofiber dispersion. The primary cellulose nanofiber dispersion was poured into a mold, frozen at -196°C for 15 min, and then vacuum freeze-dried at a vacuum degree of 1.0 Pa and a temperature of -80°C for 48 h to obtain a freeze-dried cellulose nanofiber aerogel.

[0047] The freeze-dried cellulose nanofiber aerogel was cut into pieces, dispersed in 60g deionized water, and homogenized and stirred at a speed of 4000r / min for 30min to obtain a secondary cellulose nanofiber dispersion (the solid content of the secondary cellulose nanofiber dispersion was 0.2%). 0.012g butane tetracarboxylic acid, 0.0024g sodium hypophosphite, and 0.03mL methyltrimethoxysilane were added to the secondary cellulose nanofiber dispersion, and magnetic stirring was continued at a speed of 1000r / min for 3h. The uniform dispersion was poured into a mold and allowed to stand for pre-crosslinking for 24h. Subsequently, it was pre-frozen at -196°C for 15min, and then vacuum-freeze-dried for 48h at a vacuum degree of 1.0Pa and a temperature of -80°C. The freeze-dried aerogel was placed in a vacuum oven with a vacuum degree of 1.0Pa, heated to 90°C, kept warm for 1h, then heated to 130°C, kept warm for 3h, and then cooled to room temperature and taken out to obtain a lightweight insulating cellulose nanofiber aerogel.

[0048] The density of the lightweight thermal insulation cellulose nanofiber aerogel prepared in this example is 5.4 mg / cm 3 The compression strength can reach 3.6kPa, and the sample is intact after 100 compression cycles, the rebound rate is 90%, the aerogel sample can be folded arbitrarily without falling off, and the thermal conductivity coefficient is 0.028W / (m·k), which has broad application prospects in the field of thermal insulation.

[0049] Example 2

[0050] 12 g of gelatinous cellulose nanofibers (the mass fraction of cellulose nanofibers is 3%) were added to 300 g of deionized water, and homogenized and stirred at a speed of 4000 r / min for 30 min to obtain a primary cellulose nanofiber dispersion. The primary cellulose nanofiber dispersion was poured into a mold, frozen at -196°C for 15 min, and then vacuum freeze-dried at a vacuum degree of 1.0 Pa and a temperature of -80°C for 48 h to obtain a freeze-dried cellulose nanofiber aerogel.

[0051] The freeze-dried cellulose nanofiber aerogel was cut into pieces, dispersed in 60g deionized water, and homogenized and stirred at a speed of 4000r / min for 30min to obtain a secondary cellulose nanofiber dispersion (the solid content of the secondary cellulose nanofiber dispersion was 0.6%). 0.036g butane tetracarboxylic acid, 0.0072g sodium hypophosphite, and 0.1mL methyltrimethoxysilane were added to the secondary cellulose nanofiber dispersion, and magnetic stirring was continued at a speed of 1000r / min for 3h. The uniform dispersion was poured into a mold and allowed to stand for pre-crosslinking for 24h. Then, it was pre-frozen at -196°C for 15min, and then vacuum-freeze-dried for 48h at a vacuum degree of 1.0Pa and a temperature of -80°C. The freeze-dried aerogel was placed in a vacuum oven with a vacuum degree of 1.0Pa, heated to 90°C, kept warm for 1h, then heated to 130°C, kept warm for 3h, and then cooled to room temperature and taken out to obtain a lightweight insulating cellulose nanofiber aerogel.

[0052] The density of the lightweight thermal insulation cellulose nanofiber aerogel prepared in this example is 10.3 mg / cm 3 The compression strength can reach 9.7kPa, and the sample is intact after 100 compression cycles, the rebound rate is 85%, the aerogel sample can be folded arbitrarily without falling off, and the thermal conductivity coefficient is 0.035W / (m·k), which has broad application prospects in the field of thermal insulation.

[0053] Example 3

[0054] 20 g of gelatinous cellulose nanofibers (the mass fraction of cellulose nanofibers is 3%) are added to 500 g of deionized water, and homogenized and stirred at a speed of 4000 r / min for 30 min to obtain a primary cellulose nanofiber dispersion. The primary cellulose nanofiber dispersion is poured into a mold, frozen at -196°C for 15 min, and then vacuum freeze-dried at a vacuum degree of 1.0 Pa and a temperature of -80°C for 48 h to obtain a freeze-dried cellulose nanofiber aerogel.

[0055] The freeze-dried cellulose nanofiber aerogel was cut into pieces, dispersed in 60g deionized water, and homogenized and stirred at a speed of 4000r / min for 30min to obtain a secondary cellulose nanofiber dispersion (the solid content of the secondary cellulose nanofiber dispersion was 1%). 0.12g citric acid, 0.012g sodium hypophosphite, and 0.12mL methyltrimethoxysilane were added to the secondary cellulose nanofiber dispersion, and magnetic stirring was continued at a speed of 1000r / min for 3h. The uniform dispersion was poured into a mold and allowed to stand for pre-crosslinking for 24h. Subsequently, it was pre-frozen at -196°C for 30min, and then vacuum-freeze-dried for 48h at a vacuum degree of 1.0Pa and a temperature of -80°C. The freeze-dried aerogel was placed in a vacuum oven with a vacuum degree of 1.0Pa, heated to 90°C, kept warm for 1h, then heated to 130°C, kept warm for 3h, and then cooled to room temperature and taken out to obtain a lightweight insulating cellulose nanofiber aerogel.

[0056] The density of the lightweight thermal insulation cellulose nanofiber aerogel prepared in this example is 20 mg / cm 3 The compression strength can reach 20kPa, and the sample is intact after 100 compression cycles, the rebound rate is 80%, the aerogel sample can be folded arbitrarily without falling off, and the thermal conductivity coefficient is 0.040W / (m·k), which has broad application prospects in the field of thermal insulation.

[0057] Comparative Example 1

[0058] 4g of gelatinous cellulose nanofibers (the mass fraction of cellulose nanofibers is 3%) are added to 60g of deionized water, and homogenized and stirred at a speed of 4000r / min for 30min to obtain a cellulose nanofiber dispersion. 0.012g of butane tetracarboxylic acid, 0.0024g of sodium hypophosphite, and 0.03mL of methyltrimethoxysilane are added to the cellulose nanofiber dispersion, and magnetic stirring is continued at a speed of 1000r / min for 3h, and the uniform dispersion is poured into a mold and allowed to stand for pre-crosslinking for 24h. Subsequently, it is pre-frozen at -196°C for 15min, and then vacuum freeze-dried for 48h at a vacuum degree of 1.0Pa and a temperature of -80°C.

[0059] The freeze-dried aerogel was placed in a vacuum oven with a vacuum degree of 1.0 Pa, heated to 90°C, kept warm for 1 hour, then heated to 130°C, kept warm for 3 hours, and then cooled to room temperature before being taken out to obtain a lightweight insulating cellulose nanofiber aerogel.

[0060] The density of the lightweight thermal insulation cellulose nanofiber aerogel prepared in this comparative example is 5.4 mg / cm 3 The compression strength is 2.5 kPa, and the sample is intact after 100 compression cycles, with a rebound rate of 70%, and the thermal conductivity of the aerogel sample is 0.031 W / (m·k).

[0061] Figure 1 This is a SEM image of the cellulose nanofiber aerogel prepared by secondary molding in Example 1; Figure 2 is a SEM image of the cellulose nanofiber aerogel obtained by conventional freeze drying in Comparative Example 1; Figure 1 and Figure 2 It can be seen that the cellulose nanofiber aerogel prepared by secondary molding has a large number of fiber structures, and the cellulose nanofiber aerogel obtained by conventional freeze-drying has a large number of sheet structures.

[0062] Figure 3 This is the cyclic compression curve of the cellulose nanofiber aerogel prepared by the secondary molding in Example 1; Figure 4 is the cyclic compression curve of the cellulose nanofiber aerogel obtained by conventional freeze drying in Comparative Example 1; Figure 3 and Figure 4 By comparison, the compressive strength (3.6 kPa) of the cellulose nanofiber aerogel prepared by secondary molding is much higher than that of the cellulose nanofiber aerogel prepared by conventional freeze-drying (2.5 kPa) due to the support and protection of the fiber structure.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lightweight thermal insulating cellulose nanofiber aerogel, characterized in that: The following steps are included: 1) homogenizing cellulose nanofibers in water to obtain a cellulose nanofiber dispersion, and freeze-drying the cellulose nanofiber dispersion to obtain a freeze-dried cellulose nanofiber aerogel; 2) The freeze-dried cellulose nanofiber aerogel is homogenized in water to obtain a secondary cellulose nanofiber dispersion, and the secondary cellulose nanofiber dispersion, a cross-linking agent and silane are stirred and mixed, and then subjected to static pre-cross-linking, freeze-drying and cross-linking treatment in sequence to obtain a lightweight thermal insulating cellulose nanofiber aerogel.

2. The preparation method according to claim 1, characterized in that: In step 1), the mass fraction of the cellulose nanofibers in the cellulose nanofiber dispersion is 0.01-0.15%.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the cellulose nanofibers are gel-like cellulose nanofibers, and the mass content of the cellulose nanofibers in the gel-like cellulose nanofibers is 2.5-3.5%.

4. The preparation method according to claim 3, characterized in that: The homogenization time of step 1) and step 2) is independently 15 to 45 minutes, and the homogenization speed is independently 3000 to 15000 r / min.

5. The preparation method according to claim 4, characterized in that: The freeze drying in step 1) and step 2) sequentially comprises pre-freezing and vacuum freeze drying, wherein the pre-freezing temperature is -196 to -150°C and the pre-freezing time is 10 to 60 minutes; the vacuum freeze drying temperature is -85 to -75°C and the vacuum freeze drying time is 48 to 96 hours, and the vacuum degree of the vacuum freeze drying is 0.5 to 20 Pa.

6. The preparation method according to claim 5, characterized in that: Step 2) The solid content of the secondary cellulose nanofiber dispersion is 0.1-1%, the mass ratio of the crosslinking agent to the cellulose nanofiber is 1:5-20, and the volume mass ratio of the silane to the cellulose nanofiber is 1 mL:3.5-10 g.

7. The preparation method according to claim 5 or 6, characterized in that: Step 2) the crosslinking agent comprises one or more of butanetetracarboxylic acid, isocyanate, glutaraldehyde and citric acid; the silane comprises one or more of methyltrimethoxysilane, dodecyltrimethoxysilane and perfluorodecyltrichlorosilane.

8. The preparation method according to claim 7, characterized in that: Step 2) The temperature of the cross-linking treatment is 90 to 140° C., and the time of the cross-linking treatment is 3 to 12 hours.

9. The lightweight thermal insulating cellulose nanofiber aerogel prepared by the method for preparing lightweight thermal insulating cellulose nanofiber aerogel according to any one of claims 1 to 8, characterized in that: The thermal conductivity of the lightweight thermal insulation cellulose nanofiber aerogel is 0.028-0.040 W / (m·k) and the density is 1.5-20 mg / cm 3 .

Citation Information

Patent Citations

  • Light-weight, high-strength, high-elasticity, heat-preservation and heat-insulation cellulose aerogel composite material and preparation method thereof

    CN118791781A

  • Nano cellulose hydrogel and aerogel and preparation method and application thereof

    CN108864446A

  • Preparation method of cellulose acetate nanofiber composite aerogel for heat preservation

    CN113024880A

  • Bacterial cellulose-silicon dioxide P-COF aerogel as well as preparation method and application thereof

    CN113248775A

  • Elastic cellulose aerogel and preparation method and application thereof

    CN113637234A